Pengaruh Metode Pasteurisasi terhadap Karakteristik Kimia dan Sensori Tepache - Amos Amos; Nurimansyah Nurimansyah; A. Nova Zulfahmi; Martanto Martanto; Assrorudin Assrorudin (Politeknik Negeri Lhokseumawe, 2026)
Tepache is a traditional fermented beverage made from pineapple peels that has the potential to be developed into a value-added product. Without preservation treatment, the fermentation process continues during storage, causing the acidity level to rise and limiting the shelf life. Pasteurization is one method that could potentially be applied, but its effects on the chemical and sensory characteristics of tepache have not yet been studied. This study aims to examine the effects of two pasteurization methods on the chemical and sensory characteristics of tepache. Three treatments were applied in a one-factor completely randomized design (CRD) with two replicates: a control without thermal treatment (P0), pasteurization at 63 °C for 30 minutes (P1), and pasteurization at 80 °C for 5 minutes (P2). The chemical parameters analyzed included pH, total titratable acidity (TTA), and vitamin C content, while the sensory evaluation was conducted by 20 semi-trained panelists. The chemical data were analyzed using one-way ANOVA, and the sensory data were analyzed using the Friedman test at a significance level of α = 5%. The pasteurization method had no significant effect on any of the parameters. pH values ranged from 3.460 to 3.478, TTA ranged from 0.643 to 0.733% lactic acid, and vitamin C content ranged from 50.08 to 58.66 mg/100 g. Sensory evaluations of color, aroma, taste, and overall impression also showed no significant differences, with scores ranging from near neutral to slightly liked. Both pasteurization methods produced tepache with chemical quality and sensory acceptability equivalent to the control.